Subcloning induces changes in the DNA‐methylation pattern of outgrowing Chinese hamster ovary cell colonies. Issue 6 (15th February 2021) - Weinguny, Marcus; Klanert, Gerald; Eisenhut, Peter; Lee, Isac; Timp, Winston; Borth, Nicole
Abstract: Chinese hamster ovary (CHO) cells are the most extensively used mammalian production system for biologics intended for use in humans. A critical step in the establishment of production cell lines is single cell cloning, with the objective of achieving high productivity and product quality. Despite general use, knowledge of the effects of this process is limited. Importantly, single cell cloned cells display a wide array of observed phenotypes, which so far was attributed to the instability and variability of the CHO genome. In this study we present data indicating that the emergence of diverse phenotypes during single cell cloning is associated with changes in DNA methylation patterns and transcriptomes that occur during the subcloning process. The DNA methylation pattern of each analyzed subclone, randomly picked from all outgrowing clones of the experiment, had unique changes preferentially found in regulatory regions of the genome such as enhancers, and de‐enriched in actively transcribed sequences (not including the respective promoters), indicating that these changes resulted in adaptations of the relative gene expression pattern. The transcriptome of each subclone also had a significant number of individual changes. These results indicate that epigenetic regulation is a hidden, but important player in cell line development with a major role in the establishment of high performing clones with improved characteristics for bioprocessing. Abstract : During the establishment of production cell lines, cells are subcloned to achieve high productivity and quality. Still, subclones keep displaying a wide array of phenotypes, which so far was attributed to the variability of the CHO genome. Here, we present evidence that the emergence of diverse phenotypes during subcloning is caused by changes in DNA methylation patterns and resulting transcriptomes. Shown are uniformly methylated Cs in the parent (either fully methylated =1 or fully demethylated =0) which have a different methylation state in one of the subclones. Each subclone analyzed had a different pattern of such changes, in addition to a high number of sites with minor changes in their methylation state. These results indicate the randomness of these changes and reveal epigenetic regulation as a hidden, but important player in cell line development.